2013
DOI: 10.1177/0886260513487993
|View full text |Cite
|
Sign up to set email alerts
|

Male Victims of Adult Sexual Assault

Abstract: This descriptive study aims to provide new information about the services used by sexually assaulted men and adolescent boys presenting to specialized hospital-based sexual assault programs and further insight into the factors that may be associated with their victimization. Information was collected from 38 male clients aged 12+ presenting to 29 sexual assault treatment centers in Ontario, Canada over 12 months. Variables were examined across 6 domains: time to presentation, client sociodemographics, assailan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 45 publications
2
19
1
Order By: Relevance
“…Most victims had experienced rape. Whereas previous research found that one in three male victims who referred to SACs had suffered injury that required treatment (Du Mont et al, 2013;Kimerling et al, 2002;Larsen & Hilden, 2016;Riggs et al, 2000), our study found injuries in only one in seven male victims. This discrepancy may be caused by the fact that in the Netherlands, full body examinations to check for injuries are only standardized for minors, whereas adults must disclose any injuries themselves, while other countries have standardized full body examinations for all ages.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Most victims had experienced rape. Whereas previous research found that one in three male victims who referred to SACs had suffered injury that required treatment (Du Mont et al, 2013;Kimerling et al, 2002;Larsen & Hilden, 2016;Riggs et al, 2000), our study found injuries in only one in seven male victims. This discrepancy may be caused by the fact that in the Netherlands, full body examinations to check for injuries are only standardized for minors, whereas adults must disclose any injuries themselves, while other countries have standardized full body examinations for all ages.…”
Section: Discussioncontrasting
confidence: 99%
“…Research at Canadian (Du Mont et al, 2013), Danish (Larsen & Hilden, 2016), and American SACs (Kimerling et al, 2002;Riggs et al, 2000) has consistently found the need for treatment of genital or rectal injuries in one third of male victims. About half of male victims seeking help at SACs receive forensic medical examination (FME) to collect evidence to potentially use in court (Du Mont et al, 2013;McLean et al, 2005) and about half of male victims at SACs report the assault to the police (Kimerling et al, 2002;Larsen & Hilden, 2016). The use of psychological care by men has rarely been studied and findings are mixed: A SAC in Canada reported that 76% of men sought counselling (Du Mont et al, 2013;n=38), in contrast to 48% in the United Kingdom (McLean et al, 2005;n = 376).…”
Section: Male Victims At Sacsmentioning
confidence: 99%
See 1 more Smart Citation
“…90,91 Males who present in the ED for sexual assault often have more severe injuries than women, 91,92 yet are less likely to report the assault, and less likely to use mental health services when they are offered. 90 …”
Section: Introductionmentioning
confidence: 99%
“…In a survey of 684 intimate partner violence and sexual violence agencies, 94% of responders said that they did not provide services tailored to sexual and gender minority communities ( NCAVP, 2010 ). A more recent study reported that when men seek services related to sexual violence from a health-care facility, they most often accept crisis counseling related to psychological and physical distress; medical care and treatment; prophylactic treatment for STIs and HIV (i.e., post-exposure prophylaxis or PEP, a course of treatment with antiretroviral medication, which if taken within 72 hr of exposure and completed, prevents acquisition of HIV); and counseling and testing for HIV ( Du Mont, Macdonald, White, & Turner, 2013 ).…”
mentioning
confidence: 99%